Revisores (GIST – Education and Learning Research Journal, 2023)
Gist would like to thank the following reviewers for their valuable comments and thoughtful revisionJessica Bohorquez, Birkbeck, University of London, ColombiaPaul Abraham, Simmons University, Boston, United States of AmericaCarolina Vega, Centro Colombo Americano, ColombiaDaniela Sánchez, Universidad Del Bosque, ColombiaRonald Alejandro García Vargas, Universidad del Rosario, ColombiaMohammad Kazemian, Islamic Azad University, IranSanja Škifić, University of Zadar, Croatia